Single stage high gain charge pump assisted micro-inverter. (1st December 2016) - Zhao, Ben; Abramovitz, Alexander
Highlights: An improved single stage micro-inverter topology is proposed. The modified topology employs a charge pump to attain higher voltage gain. The modified topology employs energy regeneration clamp to help recycling the leakage energy. Abstract: This article suggests an improved single stage micro-inverter topology. A modified passive network is employed to attain higher step-up of the input DC voltage. The network is built of passive elements and includes a tapped inductor charge pump. The proposed scheme also provides a solution to recycling of the leakage energy. The findings are supported by theoretical analysis, simulation and experiments.